Segregação socioespacial na Cidade de Goiás : uma leitura a partir do Residencial Tempo Novo - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
In a context in which most of the world population lives in cities, the urban theme has great relevance within Geography, and in the current circumstances, urban space has been the object of study in the most varied fields of knowledge. These considerations lead us to reflect that urban segregation is intrinsic to the constitution of the space of cities, socio-spatial segregation aims and at the reproduction of labor forces. All these processes are interconnected with the social structure, making the city a materialized expression of action of society in geographic space, through an environment and landscape that are constantly built and reconstructed. Research on Socio-Spatial Segregation in small cities has been advancing due to the importance that they occupy in the set of all Brazilian cities. In this research, an invitation is done to problematize issues of little visited scales, given that metropolitan cities end up taking considerable space in urban analyzes and little is studied about the structures of small towns. For this, the premise that part of the solution to the problems of big cities is in solving problems in small ones becomes essential. It is imperative to think of a management and application model of a new urban policy, which aims at the social promotion of individuals, guaranteeing their basic needs and access to services that dignify their lives, so that they can remain in their city and not disconnect from it, forced by economic insecurity towards the big cities. Based on the logic of proving the existence of an ongoing phenomenon, the socio-spatial segregation in the City of Goiás, this research was developed, the resolution of urban problems is in the reflection and knowledge of them. For this discussion, the sector of the city of Goiás, Residencial Tempo Novo, served as a focus for the analysis of the segregationist logic that permeates the foundation of this housing complex in 2003 to date, based on the fragmented location of the housing complex in reference to the remaining urban nucleus. This research seeks a geographical reflection to understand a phenomenon of urban reality. For the analysis of the process of socio-spatial segregation in the city of Goiás, we used as guiding points the presence and/or absence of collective and private consumption means, bodies and institutions that provide health care, education, and security. The object of this work is the understanding of the socio-spatial segregation dynamics and considerations about its conceptualization in Geography and related sciences. Considering the hypothesis of the existence of intra-urban socio-spatial segregation, the study identified the agents responsible to produce urban space, showing that socio-spatial inequalities derive not only from socioeconomic differences, but also from the place where people live. The formation of segregated spaces is a symptom of social inequality and, despite the apparent proposal for a solution to the housing deficit, there is a set of aggressive actions by the forces of power that produce the urban space, creating a segregationist socio-spatial dynamic.
Sociospatial segregation in the City of Goiás : a reading from the Residential Tempo Novo
Keywords: Segregação socioespacial; Produção do espaço urbano; Cidades pequenas; Residencial Tempo Novo – Goiás/GO; Sociospatial segregation; Production of urban space; Small towns; CIENCIAS HUMANAS::GEOGRAFIA